THE KÖNIGSBERGER LIBRARY LANDSCAPE AT THE TIME OF KRISTIJONAS DONELAITIS - WALTER, AXEL E. (Knygotyra, 2015)
At the time when Kristijonas Donelaitis visited school and went to college in Konigsberg, five public“ libraries existed in the town: the castle library (Schlossbibliothek), the university library, the city or municipal library, the library of the noble family of Wallenrodt and the library of the Secret State Chancery (Geheime Etats-Cantzley). Together, they possessed more than 25,000 volumes – the castle library with 10,000 volumes was the largest, the library of the Secret State Chancery with less than 1,000 volumes the smallest collection, while each of the remaining three libraries boasted collections of about 5,000 volumes. For a poor student who could very seldom afford the purchase of books not only these libraries were available for his reading, but – as in other cities – they also had access to private libraries, some of which even had more books than public libraries. Their owners were often professors who allowed their students to use their collections. The largest library that ever existed throughout the early modern period in Konigsberg was the one of Daniel Salthen (Salthenius, 1701–1750), who was involved as no one else in the learned education of Donelaitis: In 1731, the year of Donelaitis’ arrival he was appointed the rectorate of the cathedral school in Konigsberg, and in 1733 was given a professorship of theology at the Albertina. Large parts of the historical collections of the former Konigsberg libraries were destroyed during the Second World War. However, in the Seven Years War, when Konigsberg was occupied by the Tsar troops, complete catalogs of all “public“ libraries were made that have been preserved to our days. From Salthen’s library, as from other private libraries in Konigsberg in the mid-18th century, an auction catalog was printed. It is thus possible to reconstruct the historical collections. And despite all the destructions several thousand old prints survived the Second World War; many of them are now in the libraries of the Lithuanian Academy of Sciences and the National Library in Vilnius and can be explored there. “The Seasons” by Kristijonas Donelaitis is regarded a poetic masterpiece, the creation of which would not have been possible without a profound knowledge of ancient and contemporary European poetry. At the same time it is an innovative poem for its age, creating something new and special out of these many traditions. There seems little doubt that Donelaitis must have acquired his indisputable knowledge through reading. There is no proof whether he owned a personal library, yet its existence might certainly be presumed. Irrespective of this question the crucial period of the intellectual socialization of Donelaitis was undoubtedly the decade spent in Konigsberg. It is likely that in this decade he read many of the books whose influence can be seen in his poetry. Therefore, it is natural to think of him as a potential reader of Konigsberg libraries. The paper shows some opportunities to identify possible reading matters of Kristijonas Donelaitis on the basis of the historical catalogs of Konigsberg libraries and the still existing prints from these collections and discusses the chances to reconstruct on the basis of this material the genesis of his great poetic masterpiece more accurately than before.